Flexibility of Communal Spaces of the Osing Settlements in Kemiren Tourism Village, Banyuwangi - Made Adriana Murliana Bimar Zakharia, Ni; Ketut Agusintadewi, Ni (Universitas Ibn Khaldun Bogor, 2023)
The Osing is one of the tribes in Banyuwangi, with nomadic life history. Since the conditions change after the war against the invaders, this tribe has lived permanently. One of which is in Kemiren Village. Owing to maintaining its cultural heritage, Kemiren Village was established as a tourism village in 1996. Through this establishment, the society uses the existing spaces around the village as a space for community activities to socialize and do tourism activities. The study aims to evaluate spatial flexibility in Kemiren Village as an implementation of a sustainable tourism village's concept. An ethnographic strategy was approached from a macro perspective to see the impact of changes in social conditions on the use of the existing space in the village, particularly the village's streets. The study results revealed that the Osing in Kemiren Tourism Village had developed its tourism potential by utilizing village streets as a space for social activities and tourism attractions. According to spatial flexibility principles, four types of flexibility happened on these streets in Kemiren Village, such as adaptable, universal, movable, and responsive flexibility.